The three snow bears. - Brett, Jan, 1949- (New York : G. P. Putnamś Sons, 2007)
Retells the story of Goldilocks, set in an Inuit village and featuring a family of polar bears
Goldilocks and the three bears. English
All Juvenile
Keywords: Folklore; Polar bear--Folklore.; Bears--Folklore.